Definisi, Penyebab, Klasifikasi, dan Terapi Sindrom Dispepsia - Wildani Zakiyah; Annastya Eka Agustin; Annisa Fauziah; Nur Sa’diyyah; Galih Ibnu Mukti (Jurnal Health Sains, 2021)
Dyspepsia is a symptomatic syndrome disease characterized by pain or discomfort in the upper part or heartburn. Organic dyspepsia is caused by disorders in the gastrointestinal tract or around the gastrointestinal tract, such as the pancreas, gallbladder and others. The purpose of this study is to find out the definition, causes, classification, and therapy of dyspepsia syndrome. The method used in reviewing this article is the collection of literature from existing journal sources related to dyspepsia in general sourced from google, google scholar, and e-book using the keywords "dyspepsia", "classification of dyspepsia", "causes of dyspepsia", and "dyspepsia therapy" in literature search. Obtained organic ispepsia results occur due to organic abnormalities. In organic dyspepsia there are noticeable abnormalities seen in endoscopy of digestive tract organs such as peptic ulcer or known as peptic ulcer, gastritis, stomach cancer, gastro esophageal reflux disease (GERD), hyperacidity. The conclusion obtained is that in the cure of dyspepsia disease can be treated with pharmacological therapy which includes the use of drugs such as; antacids, anticholinergics, H2 antagonists and others. In addition, dyspepsia can also be treated with non-pharmacological therapies that include maintaining a diet, reducing stress and others.